Investigating pathways to accountability for international crimes in Africa : Comparative review of selected justice mechanisms - Roux, Mispa (University of Pretoria, 2024)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2022.